2011
DOI: 10.1159/000323759
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Cognitive Impairment and Hypertension on Total Mortality in Elderly People: The Kangwha Cohort Study

Abstract: Background: Previous studies have shown links between cognitive impairment and hypertension as well as mortality. However, combined effects of these two conditions on mortality have not been fully explored. Objective: To assess the combined effect of cognitive impairment and hypertension on all-cause mortality among the elderly people. Methods: We followed a cohort of 2,496 residents in Kangwha County, ranging in age from 64 to 101 years as of March 1994, for all-cause mortality for 11.8 years up to December 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
0
11
0
1
Order By: Relevance
“…Twenty-nine studies (Kukull et al , 1994; Arfken et al , 1995; Bruce et al , 1995; Gale et al , 1996; Agüero-Torres et al , 1999; Foley et al , 1999; Kammoun et al , 2000; Helmer et al , 2001; Stump et al , 2001; Freels et al , 2002; Ganguli et al , 2002; Feil et al , 2003; Nguyen et al , 2003; Tschanz et al , 2004; Cacciatore et al , 2005; Fitzpatrick et al , 2005; Magaziner et al , 2005; Bursi et al , 2006; Guhne et al , 2006; Llinàs-Regla et al , 2007; Lyketsos et al , 2007; Meerman et al , 2008; Rothman et al , 2008; Zekry et al , 2009; Lavretsky et al , 2010; Wang et al , 2010a; Gombojav et al , 2011; Millán-Calenti et al , 2011; Nikolova et al , 2011) compared mortality rates for persons with multiple CCs and with and without moderate-to-severe cognitive impairment or dementia. Seventeen used community-based samples and 12 used clinic-based samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-nine studies (Kukull et al , 1994; Arfken et al , 1995; Bruce et al , 1995; Gale et al , 1996; Agüero-Torres et al , 1999; Foley et al , 1999; Kammoun et al , 2000; Helmer et al , 2001; Stump et al , 2001; Freels et al , 2002; Ganguli et al , 2002; Feil et al , 2003; Nguyen et al , 2003; Tschanz et al , 2004; Cacciatore et al , 2005; Fitzpatrick et al , 2005; Magaziner et al , 2005; Bursi et al , 2006; Guhne et al , 2006; Llinàs-Regla et al , 2007; Lyketsos et al , 2007; Meerman et al , 2008; Rothman et al , 2008; Zekry et al , 2009; Lavretsky et al , 2010; Wang et al , 2010a; Gombojav et al , 2011; Millán-Calenti et al , 2011; Nikolova et al , 2011) compared mortality rates for persons with multiple CCs and with and without moderate-to-severe cognitive impairment or dementia. Seventeen used community-based samples and 12 used clinic-based samples.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (Helmer et al , 2001; Stump et al , 2001; Freels et al , 2002; Feil et al , 2003; Nguyen et al , 2003; Tschanz et al , 2004; Fitzpatrick et al , 2005; Bursi et al , 2006; Guhne et al , 2006; Llinàs-Regla et al , 2007; Meerman et al , 2008; Rothman et al , 2008; Lavretsky et al , 2010; Gombojav et al , 2011) reported the adjusted HR for significant cognitive impairment on risk of mortality (95% CI) ranging from 1.5 (1.1–2.1) (Rothman et al , 2008) to 2.99 (2.53–3.53) (Tschanz et al , 2004); covariates may have included demographics, CCs, and six other frailty criteria (Rothman et al , 2008). The percent attributable risk (PAR%) of death related to dementia diagnosis ranged from 11.8% (Guhne et al , 2006; Llinàs-Regla et al , 2007) to 16.6% (Tschanz et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large majority of articles were excluded because they were not relevant to the issue we aimed to evaluate. Among the retrieved 38 articles, 13 cohort studies met our inclusion criteria, with 870,678 participants [20][32]. Figure 1 provides a diagram of the selection process and reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with untreated and uncontrolled hypertension are at an increased risk of developing stroke, heart attack, and kidney or heart failure, which can eventually lead to death. Inadequate control of hypertension has also been associated with cognitive decline in elderly patients [5] resulting in both social and financial burdens [6]. …”
Section: Introductionmentioning
confidence: 99%